VIDEO SCRAMBLING - N. A. Laurynovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Video encryption algorithms of MPEG family with embedded unauthorized access preventing support and proposes an original video data protection technique based on scrambling using long period random sequence when source video sequence is being encoded according to the H.264\AVC (MPEG 4 Part 10) standard is proposed.